2000
DOI: 10.1002/1096-9101(2001)28:1<44::aid-lsm1015>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of solubility on laser tissue-welding with albumin solid solders

Abstract: The soluble solid solder behaved like dense liquid solder at the tissue interface. Hence, the interface strength of these two forms of solder should be similar. This correlation made it possible to identify an intrinsic limit for the weld strength of albumin solders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Hence, the fluence ($52 J/cm 2 ) characterizes the LTR of chitosan adhesives better than the radiation dose (J/mg). In contrast, the latter is more appropriate for albumin solders, which undergo a phase transition during denaturation and they require a fixed amount of energy per mole to change the protein conformation (1.2 AE 0.5 J/g) [21].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the fluence ($52 J/cm 2 ) characterizes the LTR of chitosan adhesives better than the radiation dose (J/mg). In contrast, the latter is more appropriate for albumin solders, which undergo a phase transition during denaturation and they require a fixed amount of energy per mole to change the protein conformation (1.2 AE 0.5 J/g) [21].…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously shown that a solid protein strip dissolves a few micron of its thickness when in contact with tissue moisture and therefore, is equivalent to a concentrated fluid solder at the tissue interface [5]. In this report, the solid solder was preferred over the fluid one since it allowed control of the solder thickness and surface area with much higher precision.…”
Section: Discussionmentioning
confidence: 95%
“…The major drawback of this technique was the weak tensile strength of the repairs due to the decreased solubility of the partially denatured solder. Indeed, it has recently been reported by Lauto et al that repair strength is reduced when solder solubility decreases [5].…”
Section: Introductionmentioning
confidence: 98%
“…Reports suggest a variety of contributing factors from non-covalent, covalent, and disulfide bonds through denaturation of the collagen substructure and the formation of mechanical interlocks as the protein solder and adjacent tissues denature [18,20,21]. Our experience with the BioWeld 1 device has shown that by far the most important mechanism for vascular fixation is geometric in origin rather than chemical.…”
Section: Discussionmentioning
confidence: 99%